FAKTOR YANG MEMPENGARUHI PRAKTIK MENYUSUI PADA IBU POST SECTIO CAESAREA DI RSI A. YANI SURABAYA - Uke Maharani Dewi (Universitas Nahdlatul Ulama Surabaya, 2016)
factors that affect the practice of nursing in the mother post section caesarea. Various programs to support the delivery of ASI has intensified coverage of ASI but still does not meet the expected target. Previous studies showed that breastfeeding initiation was late in babies born with sectio caesarea compared to those with vaginal delivery and prevalence of exclusive breastfeeding practice was low in the former group. The objective of this study was to define factors correlated breast feeding practice initiation on post sectio caesarea mother. 72 post sectio caesarea mothers were observed and interviewed on January 2012 to find the factors correlated with breastfeeding practice. The results showed that although 26.4% of them had previous experience in breastfeeding, only 6.9% and 29.2% of total breastfeeding is started on the first and second post sectio caesarea respectively. Support for breastfeeding practice from health workers was low, and there were significant correlation between the support and rooming conditions with breastfeeding practices (p = 0.001).